Serotonin neuromicrobiology: Psychobiotic modulation of the gut–brain axis for mental health - Nidhi Mandloi; Aarzoo; Chakkaravarthi Saravanan; Heera Ram; Bhim Pratap Singh (Ibrain, 2026)
Abstract The rise in mental health disorders has increased interest in novel natural therapeutic approaches beyond pharmacological interventions. Psychobiotics are live microorganisms that confer mental health benefits and have emerged as a promising intervention targeting the gut–brain axis. Evidence from preclinical studies demonstrated that psychobiotics can restore neurotransmitter balance by modulating pro‐inflammatory cytokines and enhancing the expression of brain‐derived neurotrophic factor. However, significant challenges remain, including the limited availability of clinical studies, determining optimal dosages, and understanding the long‐term benefits of specific psychobiotic strains and their application in food matrices. This review highlights the findings from recent studies to identify psychobiotics' capability on tryptophan metabolism and their role in facilitating the synthesis of serotonin to propose a mechanistic framework for microbe‐driven serotonin. While the eukaryotic pathways of serotonin biosynthesis are well defined, the specific mechanism by which bacteria contribute to this synthesis remains less understood; elucidating this metabolic link is essential. Beyond mechanism, this review evaluates the synergy between psychobiotics and food matrices to showcase the therapeutic approach to address the limitations of current interventions.